Sequential round-robin tournaments with multiple prizes - Christoph Laica; Arne Lauber; Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
We examine the fairness and intensity of sequential round-robin tournaments with multiple prizes. With three symmetric players and two prizes, the tournament is completely fair if and only if the second prize is valued half of the first prize, regardless of whether matches are organized as Tullock contests or as allpay auctions. For second prizes different from half of the first prize, three-player tournaments with matches organized as Tullock contests are usually fairer than tournaments with matches organized as all-pay auctions. However, unless the second prize is very small, they are less intense in the sense that players exert less ex-ante expected aggregate effort per unit of prize money. Moreover, we specify how the relative size of the second prize influences the extent and the direction of discrimination as well as the intensity of three-player tournaments. Finally, we show that there is no prize structure for which sequential round-robin tournaments with four symmetric players are completely fair in general.
Keywords: C72; D72; Z20; 330; Round-Robin Tournament; Multiple Prizes; Fairness; Intensity; Tullock Contest; All-Pay Auction